Mekanisme Penggantian Kepala Desa - Hasibuan, Siti Aisyah; Gunawan, Syafri (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
Implementation of the Regulation of the Minister of Home Affairs Number 66 of 2017 Article 8 Concerning the Mechanism of Replacement of Village Heads in Matondang Village, Ulu Barumun District, Padang Lawas Regency